Impact of omalizumab on medical cost of childhood asthma in Japan. Issue 5 (13th May 2016) - Yoshikawa, Hideki; Iwata, Mihoko; Matsuzaki, Hiroshi; Ono, Rintaro; Murakami, Yoko; Taba, Naohiko; Honjo, Satoshi; Motomura, Chikako; Odajima, Hiroshi
Abstract: Omalizumab is effective in children with severe asthma, but its impact on medical cost in Japan is not clear. We evaluated the impact of omalizumab on medical cost by comparing the pre‐ vs post‐omalizumab‐initiation medical costs of 12 children with severe asthma who received omalizumab for 2 years, and calculating incremental cost‐effectiveness ratio for omalizumab therapy. Health outcome was measured as hospital‐free days (HFD). The median total medical costs and medication fee per patient increased significantly after omalizumab initiation because of the high cost of omalizumab. The median hospitalization fee per patient, however, decreased significantly after omalizumab initiation due to reduction in hospitalization. Omalizumab led to an estimated increase of 40.8 HFD per omalizumab responder patient per 2 years. The cost was JPY 20 868 per additional HFD. Omalizumab can therefore reduce hospitalization cost in children with severe asthma in Japan.